REFERENCE GROUP INFLUENCES STUDENT TO CHOOSE MARKETING PROGRAMME AT PUBLIC HIGHER EDUCATION. CASE STUDY AT SARAWAK COUNTRY. - Norfiza, Alli (Universiti Malaysia Sarawak, (UNIMAS), 2009)
The main aim of this study is to investigate reference group that influences student to choose marketing programme. Besides that, it intends to measure whether students choose marketing programme by them self or not and to find the relationship between reference group that influences students to choose marketing programme. The scope of this study is limited to marketing students at University Malaysia Sarawak. A total of 396 were distributed to marketing students but there were only 356 questionnaires collected. Anova and correlation showed that no significant between male and female students in influences them to choose marketing programmes and there are weak relationship between individual, parents and friends reference group. Therefore, this study can be use as the reference by public higher education in order to motivated the students enhance the learning into their public higher education. Apart from that, this study also suggest the management of university to provide suitable programme for the student in order to produce the students that have a quality and not only production oriented